2016
DOI: 10.1080/21505594.2016.1227906
|View full text |Cite
|
Sign up to set email alerts
|

The Shigella ProU system is required for osmotic tolerance and virulence

Abstract: To cope with hyperosmotic stress encountered in the environments and in the host, the pathogenic as well as non-pathogenic microbes use diverse transport systems to obtain osmoprotectants. To study the role of Shigella sonnei ProU system in response to hyperosmotic stress and virulence, we constructed deletion and complementation strains of proV and used an RNAi approach to silence the whole ProU operon. We compared the response between wild type and the mutants to the hyperosmotic pressure in vitro, and asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Deletion of proP and proU in the E. coli strain HU734 resulted in slower growth in high-osmolality human urine but did not impact urinary tract colonization in mice (55). Studies of other bacteria showed that the ProU transporter is important for infection of moth larvae by Shigella sonnei (143). Also, ProP was concluded to be critical for survival of S. enterica serovar Typhimurium in desiccated environments such as stainless steel surfaces (75).…”
Section: Bacterial Pathogensmentioning
confidence: 99%
“…Deletion of proP and proU in the E. coli strain HU734 resulted in slower growth in high-osmolality human urine but did not impact urinary tract colonization in mice (55). Studies of other bacteria showed that the ProU transporter is important for infection of moth larvae by Shigella sonnei (143). Also, ProP was concluded to be critical for survival of S. enterica serovar Typhimurium in desiccated environments such as stainless steel surfaces (75).…”
Section: Bacterial Pathogensmentioning
confidence: 99%
“…In pathogenic bacteria, response to osmotic stress is a critical mechanism for survival during environmental osmotic stress as well as for establishing infection. For instance, the ProU system functions to allow S. sonnei to tolerate hyperosmotic stress in vitro , while also facilitating the survival and proliferation of the bacteria within stressful intracellular niches (Mahmoud et al, 2017 ). Herein, we observed that when exposed to hyperosmotic stress, Ssr54 was downregulated and survival of the Ssr54 deletion strain increased.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the two efflux pumps, AcrAB and MdtJI, of Shigella are reportedly associated with resistance to bile salts and the extrusion of toxic compounds (Leuzzi et al, 2015 ; Nickerson et al, 2017 ). Hence, developing strategies for tolerating changes in environmental osmolarity, is critical for pathogenic bacteria to not only permit survival during environmental osmotic stress, but also to establish infection (Mahmoud et al, 2017 ). Specifically, maintaining a stable osmotic balance between the cell cytoplasm and outer environment is an important challenge for all cell types, particularly bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, both intra-and extracellular bacterial pathogens use a variety of means to adapt to metabolic and environmental challenges that they encounter during an infection. In this regard, recent work from Mahmoud et al 1 suggest that one such environmental condition that intracellular pathogenic bacteria encounter and respond to upon entry into infected cells is cytosolic hyperosmotic stress.…”
mentioning
confidence: 99%
“…8 In recent work, Mahmoud et al, report another advance, which points to the importance of osmoregulation during intracellular infection. 1 Following up on an earlier observation with Shigella flexneri, 9 an intracellular gastrointestinal pathogen, the investigators demonstrate that the closely related Shigella sonnei ProU transport system is transcriptionally up-regulated in vitro under hyperosmotic conditions. The ProU transport system, encoded in the proVWX operon, is comprised of 3 components: ProV, an ATPase, ProW, an inner membrane protein, and ProX, a periplasmic substrate binding component, that work together to likely transport betaine and proline betaine into the Shigella cytoplasm.…”
mentioning
confidence: 99%